The Effect Of Additional Corn Husk Toward The Density Level of Light Brick - Noer Af'idah; Oktaffi Arinna Manasikana; Andhika Mayasari (JURNAL PENA SAINS, 2020)
The Light brick is an engineered product developed from the usual brick with the addition of mixed materials. Brick is one type of composite material. Many people choose to use natural fiber-reinforced composites to replace synthetic ones and composite materials engineering development. So in the technology of brick-making, natural fibers are currently used as a choice as additional material mixed to produce light bricks. Additional materials often used in light bricks include fly ash, sawdust, coconut husks, rice husks, etc. This study used corn husk waste as additional material in the light bricks making. The addition of corn husk powder can affect the mechanical properties of brick. It is shown by the more significant the percentage of corn husk powder added, the smaller the density and compressive test value of the brick produced. Meanwhile, the greater the porosity value is. The decrease in density level and compressive test value will undoubtedly affect the brick's mechanical and physical properties. The reduction in density level and mechanical properties of the brickwork can be minimized by applying an outer layer in the form of cement mortar of the products.